When a Little Bit More Makes the Difference: Expression Levels of GKRP Determines the Subcellular Localization of GK in Tanycytes - Salgado, Magdiel; Ordenes, Patricio; Villagra, Marcos; Uribe, Elena; García-Robles, María de los Angeles; Tarifeño-Saldivia, Estefanía (Frontiers in Neuroscience, 2019)
Glucose homeostasis is performed by specialized cells types that detect and respond to changes in systemic glucose concentration. Hepatocytes, β-cells and hypothalamic tanycytes are part of the glucosensor cell types, which express several proteins involved in the glucose sensing mechanism such as GLUT2, Glucokinase (GK) and Glucokinase regulatory protein (GKRP). GK catalyzes the phosphorylation of glucose to glucose-6-phosphate (G-6P), and its activity and subcellular localization are regulated by GKRP. In liver, when glucose concentration is low, GKRP binds to GK holding it in the nucleus, while the rise in glucose concentration induces a rapid export of GK from the nucleus to the cytoplasm. In contrast, hypothalamic tanycytes display inverse compartmentalization dynamic in response to glucose: a rise in the glucose concentration drives nuclear compartmentalization of GK. The underlying mechanism responsible for differential GK subcellular localization in tanycytes has not been described yet. However, it has been suggested that relative expression between GK and GKRP might play a role. To study the effects of GKRP expression levels in the subcellular localization of GK, we used insulinoma 832/13 cells and hypothalamic tanycytes to overexpress the tanycytic sequences of Gckr. By immunocytochemistry and Western blot analysis, we observed that overexpression of GKRP, independently of the cellular context, turns GK localization to a liver-like fashion, as GK is mainly localized in the nucleus in response to low glucose. Evaluating the expression levels of GKRP in relation to GK through RT-qPCR, suggest that excess of GKRP might influence the pattern of GK subcellular localization. In this sense, we propose that the low expression of GKRP (in relation to GK) observed in tanycytes is responsible, at least in part, for the compartmentalization pattern observed in this cell type. Since GKRP behaves as a GK inhibitor, the regulation of GKRP expression levels or activity in tanycytes could be used as a therapeutic target to regulate the glucosensing activity of these cells and consequently to regulate feeding behavior.